Deforestation, livelihoods, and the preconditions for sustainable management in Olancho, Honduras - Sunderlin, William D. (1997)
Growth of the national cattle herd is contributing to rapid and inappropriate deforestation in Honduras. Field research was conducted in the Department of Olancho to better understand this problem and to assess the possibilities for local interest in forest protection. A recent upsurge in the profitability of cattle farming bodes badly for the forest, but three countervailing factors could ultimately serve as the basis for community-based forest management. First, area residents have a greater appreciation for the economic and ecological functions of the forest than one might surmise, given the rapid pace of deforestation. Second, timber is a significant source of community income, thus there may be latent incentives to maintain supplies in the long term. Third, some residents will not turn to cattle farming, in spite its profitability, perhaps because of their dependence on timber marketing. Policies enacted in 1992 undermine these incipient incentives for forest custodianship. Inappropriate deforestation can be lessened through policy reforms that would enable smallhorders to conserve and manage their resource their resources over the long-term.